Cultivation of Microalgae Chlorella vulgaris in Airlift photobioreactor for Biomass Production using commercial NPK Nutrients - Ammar, Saad Hanash (Al-Khwarizmi Engineering Journal, 2017)
Airlift reactors are widely used in the chemical and biochemical applications as effective contactors for mass and heat transfer. The main advantages of airlift contactor compared with simple bubble column are ease of construction, low shear rate, high capacity, good mixing and liquid circulation without mechanical agitators and circulating pumps.In this work, growth characteristics of Chlorella vulgaris microalgae were studied in an internal loop airlift photobioreactor for biomass production. The bioreactor operated under batch and semi-continuous culture mode using commercially available 20:20:20+TE NPK fertilizer as nutrients. The experiments were conducted to evaluate the growth rate and biomass productivity of Chlorella vulgaris microalgae as affected by several factors such as nutrients concentration (20-80 mg/L), inlet air flow rate (2-8 LPM), and harvesting ratio (10-30 vol.%). The growth rate and biomass productivity of Chlorella vulgaris was determined as changes in optical density using UV-spectrophotometer. The results of batch operation showed that the growth rate of Chlorella vulgaris microalgae was increase with increasing of NPK nutrient concentration used but the access to the stationary phase of growth was delayed. The rate of growth was also increase with the increase in air flowrate to a limit then decrease. On the other hand the airlift photobioreactor can be operated in semi- continuous mode successfully by choosing the optimum conditions from the batch step which was 40 mg/L NPK nutrients concentration and 6 LPM and air flowrate. Several ratios of reactor content were harvested and the maximum biomass productivity was 0.142 g/L.day when harvested 10 vol.% every two days.